Merit System Innovation through the SIPINTER Application (Information System for Self-Assessment of Merit System Implementation) in Indonesia - Afisa, Afisa; Suswanta, Suswanta; Zaenuri, Muchamad (JURNAL ILMU SOSIAL, 2023)
This study aims to analyze the implementation and impact of the State Civil Apparatus (ASN) management innovation carried out by the State Civil Apparatus Commission (KASN) through the SIPINTER application (Information System for Self-Assessment of the Implementation of the Merit System) and its relevance in achieving good governance in Indonesia. This study used a descriptive research method with a qualitative approach, and data were obtained from official sources such as the KASN website and online news. The theory used in this study is the Public Sector Innovation Typology theory from Halvorse et al. (2005), covering (1) Creation of new services, (2) Process innovation, (3) Administrative innovation that focuses on policy change, (4) System innovation, (5) Conceptual innovation, and (6) Radical change in rationality. The results of the study show that the application of information technology in ASN management through the SIPINTER application has increased transparency, accountability, and effectiveness of ASN management at various levels of local government. Future research can carry out the development of a sustainable strategy as an important step to realize the potential of this application in the implementation of a meritocratic system in all regional and central government in Indonesia.